2020
DOI: 10.3389/fimmu.2020.01035
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Preterm Infants and the Influence of Milk Diet

Abstract: Preterm infants born before 32 weeks gestational age (GA) have high rates of late onset sepsis (LOS) and necrotizing enterocolitis (NEC) despite recent improvements in infection control and nutrition. Breast milk has a clear protective effect against both these outcomes likely due to multiple mechanisms which are not fully understood but may involve effects on both the infant's immune system and the developing gut microbiota. Congregating at the interface between the mucosal barrier and the microbiota, innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 61 publications
2
10
0
1
Order By: Relevance
“…21 Tailoring infant formula with new combinations of NDCs including HMOs might be of interest not only for babies with lower fermentability possibilities but also for example, for infants with different immune backgrounds, like preterm infants who have deviated T-lymphocyte (T-cell) responses. 22 Naïve T-cells play an important role in the defense against infections. After encountering antigen presenting cells like DCs, the naïve T-cells are activated and differentiate toward antigen specific T-cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Tailoring infant formula with new combinations of NDCs including HMOs might be of interest not only for babies with lower fermentability possibilities but also for example, for infants with different immune backgrounds, like preterm infants who have deviated T-lymphocyte (T-cell) responses. 22 Naïve T-cells play an important role in the defense against infections. After encountering antigen presenting cells like DCs, the naïve T-cells are activated and differentiate toward antigen specific T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…In preterm infants naïve T-cells skew toward a T-helper 2 (Th2) phenotype, while they have a diminished T-helper 1 (Th1) response. 22 As newborns are exposed to many new antigens, this makes them more susceptible to infections by intracellular pathogens. 22 Dietary interventions are able to restore the balance between Th1 and Th2 responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors contribute to adequate initial bacterial colonization in the newborn, including one important determinant, breast milk-based nutrition. Breast milk contains a variety of components that can affect intestinal mucosal immunity, as demonstrated in both humans and animal models of early life (46). The human lower airway microbiome forms within the first two postnatal months, and the mode of delivery determines the airway microbiota in preterm but not term births (12).…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that weight gain was not significantly affected 25 . The stimulation of Bifidobacteria was found to be associated with a reduced presence of clinically relevant gut pathogens 33 .…”
Section: Roles Of Prebiotics In Immunity Developmentmentioning
confidence: 99%